The first one? i dont know what else itd be
Answer:
5/8
Step-by-step explanation:
Answer:
Solutions:
, ![x = \frac{-3}{4} - i \sqrt{39}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-3%7D%7B4%7D%20-%20i%20%5Csqrt%7B39%7D)
Step-by-step explanation:
Given the quadratic equation, 2x² + 3x + 6 = 0, where a =2, b = 3, and c = 6:
Use the <u>quadratic equation</u> and substitute the values for a, b, and c to solve for the solutions:
![x = \frac{-b +/- \sqrt{b^{2} - 4ac} }{2a}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-b%20%2B%2F-%20%5Csqrt%7Bb%5E%7B2%7D%20-%204ac%7D%20%7D%7B2a%7D)
![x = \frac{-3 +/- \sqrt{3^{2} - 4(2)(6)} }{2(2)}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-3%20%2B%2F-%20%5Csqrt%7B3%5E%7B2%7D%20-%204%282%29%286%29%7D%20%7D%7B2%282%29%7D)
![x = \frac{-3 +/- \sqrt{9- 48} }{4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-3%20%2B%2F-%20%5Csqrt%7B9-%2048%7D%20%7D%7B4%7D)
, ![x = \frac{-3 - i \sqrt{39} }{4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-3%20-%20i%20%5Csqrt%7B39%7D%20%7D%7B4%7D)
Therefore, the solutions to the given quadratic equation are:
, ![x = -\frac{3}{4} - i \sqrt{39}](https://tex.z-dn.net/?f=x%20%3D%20-%5Cfrac%7B3%7D%7B4%7D%20-%20i%20%5Csqrt%7B39%7D)
Answer:
p= 44
/9
(44 over 9)
Step-by-step explanation:
Answer:
your answer is 0.375
Step-by-step explanation: